Privatising criminal justice: history, neoliberal penalty and the commodification of crime - Hamerton, Christopher (Routledge, 2023)
From nationalisation to privatisation, or bringing capitalism to the people -- The free market panacea, and putting the state up for sale -- Transatlantic crossing, or the appeal of American know-how in the age of risk, responsibilisation, and rising crime -- Public sector outsourcing, the contract culture and the myth of the regulatory state -- The private and public police, or there and back -- The public and private police, or back to the future -- Prison privatisation and the foundation of public privilege -- Prison privatisation and normalisation in the neoliberal state: between dispersal of decency and diffusion of duty -- The ascendency of the business ideal and the marketisation of offender services -- Interrogating the failed probation experiment, or it wasn't broken so why did they -- Try and fix it?